Exploring Smartphone-based Web User Interfaces for Appliances - Derthick, Katie; Scott, James; Villar, Nicolas; Winkler, Christian (Proceedings of MobileHCI '13, August 27 - 30 2013, Munich, Germany., 2013)
We describe the SAWUI architecture by which smartphones can easily show user interfaces for nearby appliances, with no modification or pre-installation of software on the phone, no reliance on cloud services or networking infrastructure, and modest additional hardware in the appliance. In contrast to appliances’ physical user interfaces, which are often as simple as buttons, icons and LEDs, SAWUIs leverage smartphones’ powerful UI hardware to provide personalized, self-explanatory, adaptive, and localized UIs. To explore the opportunities created by SAWUIs, we conducted a study asking designers to redesign two appliances to include SAWUIs. Task characteristics including frequency, proximity, and complexity were used in deciding whether to place functionality on the physical UI, the SAWUI, or both. Furthermore, results illustrate how, in addition to support for accomplishing tasks, SAWUIs have the potential to enrich human experiences around appliances by increasing user autonomy and supporting better integration of appliances into users’ social and personal lives.